Intermolecular Protein−RNA Interactions Revealed by 2D 31P−15N Magic Angle Spinning Solid-State NMR Spectroscopy - Jehle, Stefan; Falb, Melanie; Kirkpatrick, John P; Oschkinat, Hartmut; Rossum, Barth-Jan van; Althoff, Gerhard; Carlomagno, Teresa (Journal of the American Chemical Society, 2010)
The structural investigation of large RNP complexes by X-ray crystallography can be a difficult task due to the flexibility of the RNA and of the protein−RNA interfaces, which may hinder crystallization. In these cases, NMR spectroscopy is an attractive alternative to crystallography, although the large size of typical RNP complexes may limit the applicability of solution NMR. Solid-state NMR spectroscopy, however, is not subject to any intrinsic limitations with respect to the size of the object under investigation, with restrictions imposed solely by the sensitivity of the instrumentation. In addition, it does not require large, well-ordered crystals and can therefore be applied to flexible, partially disordered complexes. Here we show for the first time that solid-state NMR spectroscopy can be used to probe intermolecular interactions at the protein−RNA interface in RNP complexes. Distances between the 15N nuclei of the protein backbone and the 31P nuclei of the RNA backbone can be measured in TEDOR experiments and used as restraints in structure calculations. The distance measurement is accurate, as proven for the test case of the L7Ae−box C/D RNA complex, for which a crystal structure is available. The results presented here reveal the as yet unexplored potential of solid-state NMR spectroscopy in the investigation of large RNP complexes.